2011
DOI: 10.1029/2011jb008218
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of fault-fluid-hydrate system around a shale-cored anticline in deepwater Nigeria

Abstract: [1] Gas hydrates were recovered by coring at the eastern border of a shale-cored anticline in the eastern Niger Delta. To characterize the link between faults and fluid release and to identify the role of fluid flow in the gas hydrate dynamics, three piezometers were deployed for periods ranging from 387 to 435 days. Two of them were deployed along a major fault linked to a shallow hydrocarbon reservoir while the third monitored the fluid pressure in a pockmark aligned above the same major fault. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…The hydraulic diffusivity D H value, calculated from the dissipation curve corresponding to (iii) in Figure 6-a, was found equal to 1.3 10 -4 m 2 /s for a drainage path of 5 m corresponding to the depth of the sandy layer at the northern flank of the eastern fault. This unusual high D H value (4 orders of magnitude higher than normal D H values from the study zone -see Sultan et al, 2011) confirms that dissipation occurs through fractured sediments. After the dissipation of the pore pressure, pore fluid accumulation occurs for a second time with a maximum pore pressure of around 6 kPa (iv in Figure 6-a) followed by pore pressure dissipation with normal hydraulic diffusivity.…”
Section: Fluid Activities and Pore Pressure Measurementssupporting
confidence: 77%
See 4 more Smart Citations
“…The hydraulic diffusivity D H value, calculated from the dissipation curve corresponding to (iii) in Figure 6-a, was found equal to 1.3 10 -4 m 2 /s for a drainage path of 5 m corresponding to the depth of the sandy layer at the northern flank of the eastern fault. This unusual high D H value (4 orders of magnitude higher than normal D H values from the study zone -see Sultan et al, 2011) confirms that dissipation occurs through fractured sediments. After the dissipation of the pore pressure, pore fluid accumulation occurs for a second time with a maximum pore pressure of around 6 kPa (iv in Figure 6-a) followed by pore pressure dissipation with normal hydraulic diffusivity.…”
Section: Fluid Activities and Pore Pressure Measurementssupporting
confidence: 77%
“…This reference core crosses the regional reflector D60 and shows that the high amplitude characterizing this reflector can be correlated to a silty layer between 16 to 17 mbsf (Figure 2-B). In situ piezocone measurements acquired from the study area have also shown that the high amplitude reflectors (Figure 2-A) corresponds to a silty layer which is characterized by high tip resistance, high friction and low pore pressure (see Sultan et al, 2011). In the following, the Dxx reflectors presented in Figure 2 are interpreted as sandy-silty layers by extension of observations concerning D60, D50 and D30 ones.…”
Section: Geological Setting -Seafloor and Subseafloor Characterizationmentioning
confidence: 87%
See 3 more Smart Citations